Strategi Pengembangan Sumber Daya Manusia Berbasis Nilai-Nilai Islam di MTsN 1 Pangandaran - Lulu Andiani; Nurafilah Pebriyanti; Tiara Dewi Lestari; Yayu Nuraidah Solihat; Yayat Hidayat (PT. ALHAFI BERKAH INDONESIA, 2024)
This study examines the role of the school principal in developing Human Resources (HR) based on Islamic values at MTsN 1 Pangandaran. Field interview results indicate that the principal plays a central role in designing and directing HR development strategies, emphasizing the integration of Islamic values such as faith (akidah), worship (ibadah), morality (akhlak), and social conduct (muamalah) in the curriculum and educational practices. The strategy involves collaboration between the principal, vice principals, teachers, administrative staff, and the school committee in its implementation. The Islamic values applied, including integrity, work ethics, leadership, empathy, and independence, contribute to shaping students' character and creating an ethical and productive educational environment. While the impact of its implementation may not be immediate, periodic evaluations show improvements in HR quality among teachers, staff, and students. In conclusion, HR development based on Islamic values at MTsN 1 Pangandaran effectively forms individuals who are not only academically competent but also possess strong character and balance between worldly and spiritual matters.